INTERNATIONALIZATION OF PASURUAN COFFEE MSMES, ANALYSIS OF UPPSALA THEORY AND ITS APPLICATION - Maghfiroh, Rahma Ulfa; Sudarmiatin, Sudarmiatin; Bidin, Rosmiza (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study aims to analyze the application of Uppsala Theory to export MSMEs in Indonesia. The main focus of this research is to analyze the relationship between Uppsala Theory and exporting MSMEs in Indonesia. This research is important because MSMEs have a strategic role in the Indonesian economy and exportation is one of the important factors in economic growth in Indonesia. Descriptive qualitative method was used in this research, with a case study analysis on coffee MSMEs in Pasuruan, Indonesia. The results show that the internationalization process explained through Uppsala Theory can be used to explain the internationalization process of coffee MSMEs in Pasuruan. The Uppsala model is also useful in helping coffee MSMEs in Pasuruan improve their business activities in the international market